Neural induction and early patterning in vertebrates - Ozair, Mohammad Zeeshan (Wiley Interdiscip Rev Dev Biol, 2012)
In vertebrates, the development of the entire nervous system is triggered by signals from a powerful “organizing” region of the early embryo during gastrulation. This phenomenon - neural induction - was originally discovered and given conceptual definition by experimental embryologists working with the amphibian embryo. The molecular circuitry underlying neural induction, also performed in amphibians, demonstrated that elimination of ongoing TGFβ signaling in the ectoderm is the hallmark of anterior neural-fate acquisition. This observation is the basis of the “default” model of neural induction. Endogenous neural inducers are secreted proteins that act to inhibit TGFβ ligands in the dorsal ectoderm. In the ventral ectoderm, where the signaling ligands escape the inhibitors, non-neural fate is induced. Inhibition of the TGFβ pathway has been recently demonstrated to be sufficient to directly induce neural fate in mammalian embryos and pluripotent mouse and human embryonic stem cells. The molecular process that delineates neural from non-neural ectoderm is evolutionarily conserved across a broad range in the evolutionary tree. Our understanding of the role of signaling pathways (FGF, Wnt, and TGFβ) in neural induction in vertebrate embryos is now being facilitated by the availability of mouse and human embryonic stem cells.